Qualitative Phytochemical Screening, Evaluation of Antioxidant and Anti-Inflammatory Potentials of Vitex pinnata L. Leaf Extract - Sonia, Najmun Naher; Rahman , Minhajur; Biswas, Animesh (Journal of Bio-Science, 2023)
The purpose of the study was to screen phytochemicals and assess the antioxidant as well as anti-inflammatory properties of Vitex pinnata leaf extracts. Alkaloids, glycosides, tannins, terpenoids, saponins, phlobatannins, steroids, quinine, phenol, coumarins, and flavonoids were found during the phytochemical investigation. V. pinnata leaf extract exhibited an IC50 value of 154.33 µg/ml in the DPPH free radical scavenging assay (standard: IC50 = 25.48 µg/ml) IC50 value of 218.8 µg/ml in the albumin denaturation inhibition assay (standard: IC50 = 33.74 µg/ml). According to the findings, the leaves of V. pinnata contain a variety of pharmaceutically important secondary metabolites capable of scavenging DPPH and inhibiting albumin denaturation, demonstrating their antioxidant and anti-inflammatory properties. J. Bio-Sci. 30(2): 01-11, 2022